The Construction of the Migration’s Field of Study in Chile: Notes of a Reflexive and Self-Critical Exercise - Stefoni, Carolina (2017)
Along with the growth of the international migration over the last 20 years in Chile, there has been a steady increase in scientific research and publications. This academic interest has allowed the development of a field of studies that is characterized, as every field is, by a certain accumulation of knowledge, thematic diversification, theoretical discussion, approaches from different disciplines and delimitation of particular forms. The interest of this article is to analyze the scientific production on migration in Chile during this period, using two approaches: one thematic and the other analytical. In the results of this work, a reflection on the way in which the category of migration is constructed from the field of social sciences in the country and a possible thematic agenda is presented for future research.